A Utilização do software GeoGebra e da arte na aprendizagem de prismas - QUADROS, Glenda de Fátima Amorim (2023)
The presente work has the purpose of investigating and reflecting on the importance of new teaching methodologies, in particular,the use of the GeoGebra software and Arte, in Search of a meaningful learning of the students about the Space Geometry contente, especially, the subject prisms. In this way, a Project was carried out in a class of the 3rd year of High School in a public school in the city of Bragança, Pará, whose teaching methodology used was the interdisciplinarity between Mathematics and Art. During the development of activities with students, practicality, self-management, protagonism were encouraged, in addition to cooperation and autonomy worked on tasks that required forming groups. In addition, the results of the meetings, materials used, activities developed and, finally, the questionnaire containing the students’ opinions about the application of the project will be presented.